20. DIFFERENTIATED THYROID CANCER ASSOCIATED WITH HASHIMOTO'S THYROIDITIS: CHALLENGES IN THYROID-CONSERVING SURGERY (Vietnam Journal of Community Medicine, 2025)
Summary:Differentiated thyroid carcinoma in the setting of Hashimoto's thyroiditis generates a variety of morphological, histological, and functional alterations in the thyroid gland, presenting major challenges to thyroid-conserving surgery. Evaluate the pathological characteristics that influence the decision to thyroid conserving surgery.Objective: 39 patients with thyroid cancer tumors
Keywords: Thyroid cancer; lobectomy; central lymph node